Reference Values for Respiratory Parameters in General Adult Population - Zain Ilyas, Mohsana Tariq, Misdaq Batool, Sabahat Ali Sheikh, Firasha Ayub, Zara Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Reference values for maximum inspiratory pressure are varied among different studies and this variability is generalized by demographic differences and test performance measurement. Objective: To acquire a comprehensive set of Reference values for respiratory pressures in a general adult population and to evaluate possible associations with sex, age and body mass index (BMI). Methods: The study design was cross-sectional and sample was drawn through simple random sampling technique. The sample size was calculated using 584 based on parent article, divided on gender 292 participants each. Inclusion criteria was age between 18-40, both genders, Healthy people and moderately active. Exclusion criteria were Signs of ischemia/infarction, Stenosis or insufficiency of the cardiac valve, Systolic and diastolic failures. Data was collected from Sialkot, Pakistan. Basic anthropometric values for age, height, weight and BMI were measured. Spirometry values for FVC, FEV1, FEV1/FVC, VC, and PEF were measured. Descriptive measures were in the form of mean and standard deviation was calculated through SPSS version 25. Pearson Correlation between variables was also found. Results: Among male gender PEF have significant correlation (P< 0.00) with age while BMI have no significant correlation. FVC, FEV1, FEV1/FVC, VC do not show any significant correlation with age, weight, height and BMI among male gender. Among female gender PEF showed significant correlation (P< 0.00) with age only. FVC, FEV1, FEV1/FVC, VC do not show any significant correlation with age, weight, height and BMI among female gender. Clinical Significance: this research provided the knowledge about basic respiratory parameters and its correlation with anthropometric measurements. It can help develop the basis for occurrence of respiratory disturbances in long term due to deviation from normal parameters. Conclusion: Among males age, gender, height weight and BMI doesn’t affect normative values for respiratory pressure. While among females’ normative values of respiratory pressures are only affected by age. Keywords: Respiratory Pressure, Adult, Population, Reference values.